Má qualidade do sono, sonolência diurna excessiva e associação com aspectos de saúde mental em estudantes universitários - Ramos, Juliana Nunes (2018)
University students are a group vulnerable to the development of alterations in sleep habits, since they have a peculiar routine in function of the academic activities and the lifestyle characteristic of this phase. Among the main consequences associated with changes in sleep habits in university students are the increase in daytime sleepiness, reduction in quality of life, cognitive impairment, emotional changes, lower student performance and sometimes even dropout. The main objective of this dissertation was to evaluate the prevalence of poor sleep quality and excessive daytime sleepiness (EDS) and its association with mental health aspects in university students. This work consists of two manuscripts. The first article aimed to carry out a systematic review of the literature on the prevalence of poor sleep quality and EDS in university students. A total of 92 articles fulfilled the inclusion criteria of this study. The mean prevalence of poor sleep quality was 55.77% and the most frequently associated factors were: stress, anxiety, depression, smoking, alcohol use, EDS, physical inactivity, excessive use of cell phones, consumption of coffee and beverages stimulants, internet addiction and being female. As for EDS, the mean prevalence was 36.02% and the associated factors were poor sleep quality, low academic performance, presence of psychiatric disorders, consumption of alcoholic beverages and stimulants, being physically inactive and female. The second manuscript had the objective of estimating the prevalence of poor sleep quality and EDS in university students and to analyze the association of these outcomes with mental health aspects (depressive symptoms and perceived stress). A total of 1113 university students aged 16 to 25 years, enrolled in full-time courses at a public university in the Center-West region of Brazil were evaluated. The prevalence of poor sleep quality was 65.5% and EDS was 55%, with significant difference between the sexes (p <0.01, for both). In the adjusted models, moderate and high stress and the presence of depressive symptoms maintained an association with poor sleep quality (Adjusted Odds Ratio [OR] = 2.03, 5.04 and 4.51, respectively) and EDS ( ORaj = 1.67, 4.02 and 2.67, respectively). High prevalences of poor sleep quality and excessive daytime sleepiness among university students were observed, and those with moderate and high levels of perceived stress and presence of depressive symptoms were more likely to have the outcomes evaluated.